Diagnosis and Management of Female Pattern Hair Loss - Sarah Diba; Maria Mayfinna Gozali; Yuli Kurniawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Abstract Female pattern hair loss (FPHL) is the most common hair loss in post-puberty female. Prevalence of this nonscarring alopecia increases with age. The etiology of FPHL is still unclear, but hormonal and genetic factors are associated with pathogenesis of FPHL. Hormonal factor in FPHL is not as strong as in male pattern hair loss (MPHL). Clinical manifestations of FPHL are characterized by nonscarring baldness with shortening anagen phases and miniaturization of hair follicles, predominantly occur at the vertex, middle, and frontal regions. Hair shedding occurs progressively. The diagnosis of FPHL is established based on clinically. Classification of FPHL is according to Ludwig's criteria. Current FDA-approved FPHL therapy is topical minoxidil 2%, hair transplantation, and low level laser therapy (LLLT). Anti-androgen therapy still needs to be investigated further. The prognosis of FPHL is poor because the progressiveness continues with age. Long term treatment required for FPHL because it is a chronic residif disease. The treatment only prevents the progression of hair loss and does not cure.